The Effect of Coronavirus Pandemic on Tourism Industry in West Nusa Tenggara, Case Study: Travel Bureau - Kencana, Nimas (Sumber Belajar Sejahtera, 2025)
The world appeared to end in 2020 due to a remarkable Covid-19 pandemic. When COVID-19 arrived, it had an impact on every aspect of life, but particularly on the economy. This research discusses the effect of Coronavirus on the tourism industry in West Nusa Tenggara Province, Indonesia, which focus on travel bureau. This research aims to study the effect of Coronavirus on travel bureau’s activity and company’s revenue. in collaboration with ASITA, Association of The Indonesian Tours and Travel Agencies, this research qualified as descriptive research using mixed methods conveyed in grounded theory with the questionnaires and interviews as data collection methods. Results indicate that the travel bureau's revenue and package sales are significantly impacted by the coronavirus outbreak. However, this study also discovered that government assistance, including economic aid and intense program initiatives, is not equal.